Prognostic and clinicopathological significance of the Controlling Nutritional Status (CONUT) score in patients with lymphoma: a meta-analysis - Lili Li; Lihong Shou (BMJ Open)
Objectives The role of the Controlling Nutritional Status (CONUT) scores in predicting the prognosis of lymphoma cases has been extensively explored, with no consistent results. The present meta-analysis focused on accurately evaluating whether CONUT could be used to predict the prognosis of lymphoma cases and its clinicopathological value.Design The present meta-analysis was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The prognostic significance of CONUT to overall survival (OS) and progression-free survival (PFS) in lymphoma was estimated by calculating pooled HRs with 95% CIs. The relationship between CONUT and clinicopathological characteristics was measured based on pooled ORs with 95% CIs.Data sources PubMed, Web of Science, Embase and Cochrane Library databases were comprehensively searched from inception through 24 March 2023.Statistical methods Either a random-effects model or a fixed-effects model was selected depending on the level of heterogeneity among the included studies.Results This meta-analysis enrolled seven articles, containing 2060 patients with lymphoma. According to the pooled analysis, a higher CONUT score significantly predicted poor OS (HR=1.94, 95% CI 1.46 to 2.57, p<0.001) as well as poorer PFS (HR=1.51, 95% CI 1.04 to 2.20, p=0.031). Furthermore, according to the combined analysis, a higher CONUT score was significantly associated with Ann Arbor stages III–IV (OR=3.75, 95% CI 2.96 to 4.75, p<0.001), an Eastern Cooperative Oncology Group performance status of 2–4 (OR=5.14, 95% CI 3.97 to 6.65, p<0.001), high-intermediate/high National Comprehensive Cancer Network International Prognostic Index (OR=8.05, 95% CI 5.11 to 12.66, p<0.001), B symptoms (OR=4.97, 95% CI 2.89 to 8.52, p<0.001), extranodal disease (OR=3.25, 95% CI 2.24 to 4.70, p<0.001), bone marrow involvement (OR=4.86, 95% CI 3.25 to 7.27, p<0.001) and elevated lactate dehydrogenase levels (OR=3.21, 95% CI 2.37 to 4.34, p<0.001).Conclusions According to our results, higher CONUT scores were significantly associated with poor OS and PFS in lymphoma.